Quercetin declines plasma exposure of metoprolol tartrate in the rat model - Siva R Challa; Venkatesh R Challa; Satheesh K Ragam (Wolters Kluwer Medknow Publications, 2014)
The study was undertaken to evaluate the effect of quercetin on the pharmacokinetics of Metoprolol tartrate. A single dose in vivo pharmacokinetic study was carried out in rat models. In this study, rats were treated with quercetin (10 mg/kg) and metoprolol tartrate (20 mg/kg) orally and blood samples were collected 0, 0.25, 0.5, 0.75, 1, 1.5, 2, 4, 8, 12 h post treatment. Plasma concentration of metoprolol tartrate was estimated using reverse phase-high-performance liquid chromatography method. Area under the plasma concentration-time curve (AUC 0-12 ) of metoprolol has significantly (P < 0.001) decreased by 9.8 times in the metoprolol and quercetin combination group (9434.65 ± 3525.02) when compared with AUC 0-12 metoprolol of metoprolol-alone treated group (962.17 ± 242.81). AUC 0-∞ of metoprolol has significantly (P < 0.001) decreased by 14.9 times in the combination group (16670.79 ± 12129.06) in comparison to AUC 0-∞ of metoprolol of metoprolol-alone treated group (1113.68 ± 441.83). the results obtained herein indicate that quercetin remarkably declines the plasma exposure of metoprolol when concomitantly administered by oral route.